A nanoparticle-preparation kit using ethylene glycol-based block copolymers with a common temperature-responsive block. Issue 47 (22nd November 2017) - Kotsuchibashi, Yohei; Lee, Chun Man; Constantinescu, Iren; Takeuchi, Lily E.; Vappala, Sreeparna; Kizhakkedathu, Jayachandran N.; Narain, Ravin; Ebara, Mitsuhiro; Aoyagi, Takao
Abstract : A nanoparticle-preparation kit system using ethylene glycol-based block copolymers with a common temperature-responsive block was developed. Abstract : A nanoparticle-preparation kit system for producing desired nanoparticles using ethylene glycol-based block copolymers with a common temperature-responsive block was developed. The injected nanoparticles were found to accumulate in the tumor tissue and showed high blood biocompatibility.